FORMULASI PEMBAGIAN WARISAN 2:1 DALAM PERSPEKTIF EPISTEMOLOGI AL-JABIRI - Riyanta, Riyanta (Musawa Jurnal Studi Gender dan Islam, 2011)
This article discusses the issue of women in the family with respects to inheritance. In this context, what is discussed are contemporary thoughts, with the hopes of achieving new ideas. The formulation of 2:1 ratio for menÂ  and women are seen by classical ulama(s) as something final. In the words of Al-Jabiri, this view is counterintuitive to textual understanding. In his perspective, this formula could still change, due to the trans-historic nature ofÂ  the application of the Quran. This view is in contrast to the burhani school of thought. With many social changes in society, it could very well be that women could receive more inheritance than men.